Globalization and its terrors - Brennan, Teresa, 1952-2003 (Routledge, 2003)
In this elegant, lucidly argued account, Teresa Brennan argues that the evidence already exists that globalisation has for years been harming not just the poor of the third world but also its alleged beneficiaries in the affluent west.